Correlation between bacterial diversity and flavor substances in Longgang soy sauce - Yan, Yongheng; Zhang, Min; Zhang, Yingchao; Zhang, Xuelin; Zhang, Xingrong; Zhao, Xiangying; Xu, Hui; Huang, Yanhong (Bioscience, biotechnology, and biochemistry, 2023)
ABSTRACT Longgang soy sauce is one of the traditional fermented condiments in China, but its bacterial community succession and its unique flavor development during the fermentation process are not well-investigated. This study evaluated the bacterial diversity, flavor changes, and their correlation during the fermentation of Longgang soy sauce. The results showed that Weissella was the dominant bacterial genus in the fermentation stage of sauce fermented grains. In the first 31 days of the moromi fermentation stage, a variety of bacterial genera such as Weissella, Halomonas, Bacteroides, Pseudomonas, and Tetragenococcus were the dominant bacteria. Our results showed that these bacteria have a significantly positive correlation with phenylethyl alcohol, ethyl acetate, and 3-methyl-1-butanol. As the fermentation progressed, a flora structure with Halomonas as the main bacterial genus was formed. This genus exhibited a significantly positive and positive correlation with 1-octanol, ethyl palmitate, heptanol, and 2-nonanol, which are the unique flavor components of Longgang soy sauce. Graphical Abstract Graphical Abstract Microbial community structure and its correlation with volatile flavor components during soy sauce fermentation.